Kebiasaan sarapan tidak berhubungan dengan status gizi anak sekolah dasar di Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur - Irma Yunawati; Hamam Hadi; Madarina Julia (Alma Ata University Press, 2015)
ABSTRACTBackground: School age children are the future generation. Improvement the quality of human resources should be done early. One of factors affecting the quality of human resources is the nutritional status. Breakfast contributes in nutritional intake (15-25% RDA). Skipping of breakfast makes the body decreasing of glucose. It makes body to unload supplies of energy from fat tissue and cause of weight reduction.Objectives: To determine the relationship between breakfast habits with the nutritional status of elementary school children in Nusa Tenggara Timur Province.Methods: This was an observational study with cross-sectional design. This study used the secondary data of Alma Ata Centre for Healthy Life and Food (ACHEAF) 2013. The subjects were children from elementary school of classes between II-VI in Amanuban Barat and Kie Subdistrict, Timor Tengah SelatanDistrict with total sample of 313 students. Sample were selected by cluster random sampling technique using computer generated random number software. Data analysis used chi-square test with a confidence interval (CI) of 95% to the level of significance of p<0.05. Analysis by logistic regression was done if itshowed significance result.Results: The proportion of breakfast habits of school children was 82.11%. Most widely consumed breakfast type (78,32%) was rice (rice porridge and rice) and the other (21.68%) were non-rice eating breakfast (bose corn, yam/cassava, boiled bananas, instant noodles, corn porridge, bread/cooky). The contribution of breakfast energy intake is 13.94% RDA and protein intake was 14.4% RDA. There was no relationship between breakfast habits and nutritional status of elementary school children.Conclusions: Breakfast habits was not related with the nutritional status of school children in Amanuban Barat and Kie Sub-district.KEYWORDS: breakfast habits, nutritional status, school childrenABSTRAKLatar belakang: Anak usia sekolah merupakan generasi penerus bangsa. Upaya peningkatan kualitas sumber daya manusia (SDM) harus dilakukan sejak dini. Salah satu faktor yang mempengaruhi kualitas SDM yaitu status gizi. Sarapan memiliki kontribusi dalam memenuhi asupan gizi, menyumbangkan 15-25% AKG. Melewatkan sarapan membuat tubuh kekurangan glukosa sehingga tubuh membongkar persediaan tenaga dari jaringan lemak tubuh dan menyebabkan penurunan berat badan.Tujuan: Mengetahui hubungan kebiasaan sarapan terhadap status gizi anak sekolah dasar di Kabupaten Timor Tengah Selatan Provinsi Nusa Tenggara Timur.Metode: Jenis penelitian ini adalah observasional dengan rancangan cross sectional. Penelitian ini menggunakan data sekunder Alma Ata Centre for Healthy Life and Food (ACHEAF ) 2013. Subjek penelitian adalah anak sekolah dasar kelas II-VI di Kecamatan Amanuban Barat dan Kie, Kabupaten Timor Tengah Selatan dengan total sampel sebanyak 313 siswa. Pengambilan sampel dilakukan dengan teknik cluster random sampling menggunakan software computer generated random number. Analisis data menggunakan uji chi-square dengan confi dence interval (CI) 95% pada tingkat kemaknaan p<0,05 dan hasil analisis data yang bemakna dilanjutkan dengan uji regresi logistik.Hasil: Proporsi kebiasaan sarapan anak sekolah adalah 82,11%. Jenis sarapan yang paling banyak dikonsumsi adalah sarapan beras (bubur nasi dan nasi) sebesar 78,32% dan sebanyak 21,68% mengonsumsi sarapan non-beras (jagung bose, ubi/singkong, pisang rebus, mie instan, bubur jagung, roti/kue). Kontribusi asupan energi sarapan sebesar 13,94% AKG dan asupan protein sarapan sebesar 14,4% AKG. Tidak ada hubungan antara kebiasaan sarapan dengan status gizi pada anak sekolah.Kesimpulan: Kebiasaan sarapan tidak berhubungan dengan status gizi anak sekolah di Kecamatan Amanuban Barat dan Kie.KATA KUNCI: kebiasaan sarapan, anak sekolah, status gizi